Madrasa and Its Development in Nigeria - Abdullahi Ibrahim Sani; Cecep Anwar (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2020)
This study aims to describe the development of madrasa education system in African continent. It also explores the development of madrasa in Taraba State, Nigeria. This research used a descriptive method. The results showed that in African continent, madrasa institutions had their historical developments, financial support and how British colonial influenced their development. In Nigeria, madrasa institutions have had similar developments with their counterparts from other countries in the African continent. British colonialism has reduced the supremacy of madrasa in terms of financial and managerial capacity. In Taraba State, Nigeria, there are several different forms of traditional non-formal Islamic education. Their forms include madrasa qur'anic college with the evolutionary development around Alaramma; madrasa whose mobility is limited; and Islamic school. The three educational institutions are recognized by the government and they have experienced modernization in terms of their management for the Qur'an program and their Western infrastructure use.